The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/1063426619885862
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Aggression Among Students With Emotional and Behavioral Disorders: Teacher Perceptions of Harm, Levels of Concern, and Relationship With Certification Status

Abstract: Students who exhibit emotional and behavioral disorders (EBD) typically have high frequencies of disruptive and noncompliant behavior including physical and verbal aggression (VA). Physical aggression attracts great concern from school professionals yet VA is often overlooked, despite being a highly pervasive and harmful social act. We surveyed 279 first to 12th grade teachers of students with EBD to assess their perceptions about the harmfulness of VA, students’ intent to harm, their concern about the frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 60 publications
(99 reference statements)
0
14
0
Order By: Relevance
“…Only about 3% of the teachers surveyed felt that students with EBD very often used VA with the intent to harm another student. Succinctly, while teachers felt VA was somewhat to very harmful, they also perceived that students with EBD were mostly just kidding around and not intending to hurt others when perpetrating VA. Smith et al (2020) also found that teachers believed comments about student appearance were harmful for students with EBD (60%) and a majority of teachers indicated that insulting names were very harmful (65%). Although this finding is encouraging, teachers must also understand that verbal exchanges that appear to be innocuous may be perceived by the victim as harmful.…”
Section: Va Locations and Teacher Perceptionsmentioning
confidence: 95%
See 4 more Smart Citations
“…Only about 3% of the teachers surveyed felt that students with EBD very often used VA with the intent to harm another student. Succinctly, while teachers felt VA was somewhat to very harmful, they also perceived that students with EBD were mostly just kidding around and not intending to hurt others when perpetrating VA. Smith et al (2020) also found that teachers believed comments about student appearance were harmful for students with EBD (60%) and a majority of teachers indicated that insulting names were very harmful (65%). Although this finding is encouraging, teachers must also understand that verbal exchanges that appear to be innocuous may be perceived by the victim as harmful.…”
Section: Va Locations and Teacher Perceptionsmentioning
confidence: 95%
“…Although recognition of the harmful nature of VA is critical, a more robust and nuanced understanding of the harmfulness of VA is also necessary. For example, in a study of teachers who work with students with EBD, Smith et al (2020) found the large majority of teacher respondents believed VA was somewhat to very harmful, but just under half of teachers indicated that students with EBD never or rarely committed acts of VA with the intent to harm (48%). Only about 3% of the teachers surveyed felt that students with EBD very often used VA with the intent to harm another student.…”
Section: Va Locations and Teacher Perceptionsmentioning
confidence: 99%
See 3 more Smart Citations